Determinants of self-rated health of Francophone seniors in a minority situation in Canada - Alimezelli, Hubert Tote; Leis, Anne; Karunanayake, Chandima; Denis, Wilfrid (Linguistic Minorites and Society, 2013)
Résumé La tendance actuelle montre que les institutions des services de santé et les gouvernements répondent de façon inadéquate aux besoins de plus en plus nombreux d’accès aux services de santé par les populations vieillissantes du Canada et d’autres pays développés. Après l’analyse de l’enquête post-censitaire 2006 de Statistiques Canada sur la Vitalité des Minorités de Langue Officielle, cette étude démontre qu’outre l’age, et en plus d’autres déterminants, les barrières linguistiques auxquelles font face les aînés de langue officielle en situation minoritaire affectent davantage l’autoévaluation de leur santé. Cette étude suggère quelques pistes de solution dont la compréhension des réalités contextuelles, l’amélioration de l’environnement linguistique et des services de santé dans la langue minoritaire. Mots-clés : déterminants de la santé, statut minoritaire, santé perçue, minorités linguistiques, aînés Abstract Current trends show that governments and health institutions in Canada and other developed nations are responding inadequately to the growing need for health services of the increasingly aging population. The Analysis of Statistics Canada’s 2006 post-census Survey on the Vitality of Official Language Minorities show that in addition to age and other socio-demographic determinants, linguistic barriers affect the self-rated health of seniors of official languages living in a minority situation. This study suggests among other things a greater understanding of Official language minorities’ contextual realities, the improvement of both the linguistic environment and services in the minority language. Keywords: health determinants, minority status, self-rated health, linguistic minorities, older adults

Co-development of a Web-based hub (eSocial-hub) to combat social isolation and loneliness in Francophone and Anglophone seniors in linguistic minority context (Quebec, Manitoba, and New Brunswick): Protocol for a mixed methods interventional study - Beogo, Irissa; Ramdé, Jean; Nguemeleu Tchouaket, Eric; Sia, Drissa; Bationo, Nenila Jean-Claude; Collin, Stéphanie; Anne, Abdoulaye; Gagnon, Marie-Pierre (JMIR Research Protocols, 2021)
Background: The first wave of the COVID-19 pandemic has severely hit Canadian nursing facilities (81% of deaths). To this toll, public health measures (eg, visitation restriction) have subsequently deepened the social isolation and loneliness of residents in nursing facilities (NFs), especially those in linguistic minority settings: Anglophone institutions in Quebec and Francophone institutions outside Quebec. However, very few COVID-19 initiatives targeting these populations specifically have been documented. Given the limited number of NFs serving linguistic minorities in Canadian populations, families and loved ones often live far from these facilities, sometimes even in other provinces. This context places the digital solutions as particularly relevant for the present COVID-19 pandemic as well as in the post–COVID-19 era. Objective: This project aims to co-develop a virtual community of practice through a web-based platform (eSocial-hub) to combat social isolation and loneliness among the older people in linguistic minority settings in Canada. Methods: An interventional study using a sequential mixed methods design will be conducted. Four purposely selected NFs will be included, 2 among facilities in Manitoba and 2 in New Brunswick; and 2 Anglophone NFs in Quebec will serve as knowledge users. The development of eSocial-hub will include an experimental 4-month phase involving the following end users: (1) older people (n=3 per NF), (2) families of the participating older people (n=3 per NF), and (3) frontline staff (nurse and health care aid; n=2 per NF). Results: Activities and solutions aiming at reducing social isolation and loneliness will be implemented and then evaluated with the project stakeholders, and the best practices generated. The assessment will be conducted using indicators derived from the 5 domains of the Consolidated Framework for Implementation Research. The project will be led by an interdisciplinary team and will involve a multisectoral partnership. Conclusions: The project will develop a promising and generalizable solution that uses virtual technology to help reduce social isolation and loneliness among the older people.

Améliorer la santé et le bien-être des Madelinots anglophones. Une évaluation des besoins : mieux comprendre la situation actuelle des aînés - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Anglophone Magdalen Islanders, 2017)

Multilingualism (but not always bilingualism) delays the onset of Alzheimer disease: Evidence from a bilingual community - Chertkow, Howard; Whitehead, Victor; Phillips, Natalie; Wolfson, Christina; Atherton, Julie; Bergman, Howard (Alzheimer Disease and Associated Disorders, 2010)
A recent paper by Bialystok et al in Neuropsychologia (vol. 45, pgs. 459 to 464) suggested that early bilingualism produced a statistically significant 4.1-year delay in onset of memory loss symptoms in older individuals with Alzheimer disease, possibly reflecting an increase in the cognitive reserve of these individuals. That study focused on multilingual elderly patients of whom 90% were immigrants. Our memory clinic, in Montreal Canada, has the advantage of having a large set of individuals who are either multilingual immigrants to Canada, or who are nonimmigrants but raised in both official languages of Canada—French and English. We thus attempted to replicate the above findings using a larger cohort in a different setting. We examined age at diagnosis of Alzheimer disease and age at symptom onset for all unilingual versus multilingual participants, and then for those who were nonimmigrant English/French bilinguals. Overall, we found a small but significant protective effect of more than 2 languages spoken, but we found no significant benefit in bilinguals overall in relation to age at diagnosis or age at symptom onset. However, in the immigrant group, the results mirrored those of Bialystok et al with 2 or more languages delaying the diagnosis of Alzheimer disease by almost 5 years. A trend toward the same effect was also seen in nonimmigrants whose first language was French. In contrast, in nonimmigrants whose first language was English, no such effect was found. These results are discussed in relation to the earlier findings and the theory of cognitive reserve.

Bien vieillir dans sa langue, sa culture et sa communauté. Soutien d’institutions fédérales clés et portrait des aînés anglophones du Québec - Commissariat aux langues officielles (Gouvernement du Canada, 2013)

Promoting the health and well-being of English-speaking Seniors in Quebec. A community model (infographic) - Community Health And Social Services Network/Réseau communautaire de santé et de services sociaux (2019)

« I don’t think that’s the way healthcare for an 85 and an 88-year-old should be done. » L’accès aux services de santé et aux services sociaux des aînés anglophones vivant hors Montréal : état de la situation [thèse de maîtrise, Université de Sherbrooke] - Ethier, Alexandra (Université de Sherbrooke, 2020)
Les aînés anglophones du Québec hors Montréal ont un accès variable aux services de santé et services sociaux (SSSS). C’est pourquoi notre recherche explore l’accès aux SSSS pour les aînés anglophones vivant hors Montréal. Spécifiquement, nous décrivons les facteurs (facilitateurs et barrières) influençant l’accès aux SSSS. Ainsi, nous avons conduit une recherche qualitative de type étude de cas unique imbriquée. Nous avons collecté les données à l’aide d’entretiens semi-dirigés audio-enregistrés, d’un questionnaire sociodémographique et d’un journal de bord. Nous avons transcrit, puis analysé thématiquement les entretiens et avons analysé les données sociodémographiques par statistiques descriptives. Les 10 aînés rencontrés nous ont permis d’identifier 11 facteurs divisés en 6 facilitateurs et 8 barrières influençant l’accès aux SSSS. Les plus signifiants sont la concordance (facilitateur) ou la non-concordance (barrière) de la langue de l’aîné avec le travailleur des SSSS, où la nonconcordance mène à des consentements aux interventions non valides. Également, le facteur présence minoritaire, c’est-à-dire la concentration de la population anglophone, affecte les opportunités sociales des aînés. Ce facteur est un facilitateur lorsque fort et une barrière, lorsque faible. Enfin, des SSSS peu « amis » des aînés anglophones, définis comme un système de SSSS complexe à naviguer lorsque la langue des aînés et leurs caractéristiques personnelles ne sont pas prises en considération, constituent également une barrière. Les résultats de cette recherche informent sur les actions à poser pour faciliter l’accès aux SSSS de ces aînés anglophones et suggèrent des améliorations bénéfiques pour l’ensemble de la population.

Strategies to access health and social services for English-speaking older adults in Quebec: A qualitative case study - Ethier, Alexandra; Carrier, Annie (Canadian Social Work Review, 2023)
Considering that French is the dominant language in Quebec, that relatively few francophone providers of health and social services are able to speak English, and that English-speaking older adults (OAs) have low levels of bilingualism, anglophone OAs are more likely than their francophone peers to face language barriers when accessing health and social services. However, little is known about the strategies English-speaking OAs put into place to overcome the difficulties encountered due to language barriers when they access these services. We therefore aimed to document the strategies used by English-speaking OAs when, due to language barriers, they faced difficulties in accessing health and social services. We conducted a qualitative case study with ten English-speaking OAs in the Eastern Townships in Quebec. Through interviews and document reviews, we collected data which we then analyzed thematically. We identified seven strategies used by English-speaking OAs: investigating for health- and access-related information in English, creating their own services, entering the health and social services system offered in French, entering the health and social services system with help from others, putting the responsibility of overcoming the language barrier on the provider, splitting that responsibility, and taking on the responsibility. Our results highlight a potential burden associated with the involvement of the English-speaking community in enabling English-speaking OAs to access health and social services. Keywords: access, health services, social services, official language minority, language barriers, strategies

Profil statistique 2016 des personnes âgées francophones au Canada : faits saillants [infographie] - Fédération des aînées et aînés francophones du Canada (2019)

Profil statistique 2016 des personnes âgées francophones au Canada [Rapport] - Fédération des aînées et aînés francophones du Canada (2019)

Community involvement of seniors in the Eastern Townships - Gosselin, Chedly; Viens, Caroline (Journal of Eastern Townships Studies, 2006)
This paper explores Anglophone seniors' participation within the community of the Estrie region of Quebec. A healthy relationship between Anglophone and Francophone communities improves access to state health and social services and relieves the social isolation of those living in rural areas. Immigrant migration to the area as well as out-migration of young Anglophones is profoundly affecting the delivery of health and social services as well as changing family, community, nation, culture and what it means to be a citizen.

Protocole d’évaluation de la sécurité à domicile (PESAD) : version francophone du SAFER-HOME v.3 - Hébert, Michèle; Brasset-Latulippe, Anne; Bourgault-Côté, Sylvianne; Meilleur, Valérie; Chiu, Teresa (Francophonies d'Amérique, 2009)
Les intervenants de la santé sont appelés à se prononcer sur la sécurité des aînés vivant à domicile et ils ont, à cet effet, très peu d’outils francophones à leur disposition. Le Protocole d’évaluation de la sécurité à domicile (PESAD) est issu de la traduction et de la validation transculturelle du SAFER-HOME. Le processus de validation et l’étude de la fidélité des résultats ont mis en lumière un outil intéressant et possédant de bonnes qualités métrologiques. Il permet aux intervenants francophones d’obtenir des résultats d’évaluation complets et rigoureux relativement à la sécurité à domicile des aînés francophones.

Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux - Hsu, Amy. T.; Ménard, Alixe; Scott, Mary (Université d'Ottawa et Institut de recherche Bruyère, 2022)

Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Hsu, Amy; Ménard, Alixe; Scott, Mary (Bruyère Research Institut, 2022)

Promoting the health and well-being of English-speaking seniors in Quebec. A community model - Kueber, Rusell (Community Health and Social Services Network, 2019)

Promotion de la santé et du bien-être des aînés d’expression anglaise du Québec : un modèle communautaire - Kueber, Russell (Réseau communautaire de santé et de services sociaux, 2019)

Comprendre l'expérience des soins de longue durée des minorités de langue officielle au Canada : une analyse de l'environnement | Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Ménard, Alixe; Scott, Mary; Hsu, Amy T. (2022)

Social exclusion among official language minority older adults: A rapid review of the literature in Canada, Finland and Wales - Nyqvist, Fredica; Häkkinen, Emilia; Renaud, Alexandre; Bouchard, Louise; Prys, Cynog (Journal of Cross-Cultural Gerontology, 2021)
It has been suggested that older adults from minority linguistic and ethnic communities face higher risks of being socially excluded. The aim of this review was, therefore, to explore and review social exclusion studies conducted among official language minority older adults in three countries, namely Canada, Finland and Wales. A rapid review approach was used to review scientific literature in line with six social exclusion domains. The literature searches were made in Finnish, Swedish, English, French and Welsh and were restricted to research published within the timeline of 2001 – September 2019 and yielded 42 articles. The included studies were categorized into three different domains: socioeconomic influences, social participation and societal conditions. Converging and diverging patterns of social exclusion in old age were identified between the linguistic minorities. Linguistic barriers regarding access to health care and receiving health information were common across the three linguistic contexts, whereas exclusion from social participation was noticed amongst the linguistic minorities in Canada and Wales. Some connections between belonging to a linguistic minority and being exposed to a lower socioeconomic status and higher poverty risk were made, however, these findings were not robust across all three countries. The findings indicated that experiences of exclusion could be considered fairly common among linguistic minority older adults. We conclude that the research evidence presented in the review sheds light on issues of social inequality in old age between linguistic majorities and minorities, thus identifying important aspects of social exclusion to guide future research as well as policy and practice.

Enjoying your senior years in your own language, culture and community. Federal support from key institutions and a portrait of English-speaking seniors in Quebec - Office of the commissioner of official languages (Federal support from key institutions and a portrait of English-speaking seniors in Quebec, 2013)

Socio-demographic profile of the population aged 65 and over. Province of Québec. Based on the 2016 census of Canada - Pocock, Joanne (Community Health and Social Services Network, 2018)

Promotion de la santé et du bien-être des aînés d'expression anglaise du Québec. Un modèle communautaire( infographie) - Réseau communautaire de santé et de services sociaux/Community Health and Social Services Network (2019)

Évaluation des services communautaires pour les aînées et aînés d’expression anglaise de Gaspésie-îles-de-la-Madeleine - Richardson, Mary (2019)

Language related difficulties experienced by caregivers of English-speaking seniors in Quebec - Sanderson, Duncan (SAGE Open, 2020)
Little research has examined communication problems between speakers of official minority languages (patients or caregivers) and health care providers. The objective of this research was to identify the types of issues experienced by English-speaking caregivers of seniors in Quebec, as they interact with French-speaking health care providers. The majority of the caregivers interviewed indicated that they were satisfied with physicians’ interaction with the seniors they cared for. However, problems included health care providers who do not or who refuse to speak English, hospice personnel with insufficient English, anxiety about speaking to personnel in French, traveling to receive services in English, acting as an informal interpreter, receiving written documents in French, scheduling appointments through French-only phone systems or receptionists, and discrimination. The main finding is that in Quebec, language asymmetry might create additional stresses for an English-speaking caregiver, who is already likely to be stressed because of their caregiver role.

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)

Pratique # 11 : The Information and Support Guide for Caregivers (Québec) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 15 : Le volet « santé et services sociaux » de l’Association des Townshippers (Québec) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Directory of innovative practices in health and social services in official language minority contexts - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann; Dagnogo, Djenaba Sarah; Michel, Jean Nephetaly

Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann; Dagnogo, Djenaba Sarah; Michel, Jean Nephetaly

Culture, language and self- assesments of future health: Anglophones and Francophones in Quebec’s Eastern Townships - Stout, Dale; Charpentier, Claude; Chiasson, Myriam; Filion, Emmalie (Journal of Eastern Townships Studies, 2009)
This study examines subjective ratings of health (SRH) by Francophones and Anglophones living in the Eastern Townships. Global self-ratings of health are regarded as sensitive predictors of future health states, mortality, functional decline and disability, and utilization of the health-care system. Yet despite their pragmatic value, SRH are poorly understood. Along with a spontaneous monitoring of present health states, culture and language are listed as determinants of SRH. Few studies exist, however, that clearly delineate the direction and degree of effect that culture and language have on SRH. Adopting a temporal assessment of SRH, we asked 358 Anglophones (N=176) and Francophones (N=171) from the Eastern Townships, aged 18 to 95, to rate their health in the past, present, and future. To isolate culture and language effects we also asked participants to rate their future health if they “remained in Quebec”. Results revealed a significant interaction between age and temporal ratings of health (SRH). Turning to the effects of location (unspecified or “in Quebec”) on future health ratings, there was a significant interaction with language. Post hoc tests revealed no significant differences in Francophones’ future health ratings (unspecified or “in Quebec”) but a significant ratings drop was noted for Anglophones if they “remained in Quebec”. After controlling for bilingualism, this interaction remained statistically significant.

The effects of age and culture on subjective well-being: A case study in the Eastern Townships - Stout, Dale; Filion, Emmalie; Chiasson, Myriam; de Man, Anton; Charpentier, Claude; Pope, Megan (Journal of Eastern Townships Studies, 2008)
The present study of diachronous ratings of subjective well-being (SWB) was modeled on research undertaken by Staudinger, Bluck & Herzberg (2003). In addition, we were interested in determining the effects of culture and context (where one lives) on SWB ratings. To gage these effects, we included the factor of mother tongue and altered the Life Satisfaction Questionnaire by adding a question concerning expected well-being in Quebec. We asked 350 Anglophones and Francophones from the Eastern Townships, aged 18 to 95, to rate their SWB in the past, present, future, and future ‘in Quebec’. The results concerning the effects of chronological age on diachronistic SWB ratings followed the patterns of previous research: young people (aged 18–38) rate past SWB lower than present SWB and future SWB much higher; middle-aged people (aged 39–64) rate their SWB the same regardless of time; And the elderly (67–95) rated past SWB higher than the present and their future SWB much lower. There were no differences between Anglophones or Francophones. Further analysis revealed the disturbing finding that the oldest participants rated their current SWB significantly lower than the other two age groups. In the second half of our study we found that by simply asking Francophones and Anglophones to rate their SWB in the future – first unspecified as to location, and then in a future ‘if they stay in Quebec’ – produced different response patterns. Both future SWB ratings were the same for Francophones, indicating that the questions were simply redundant. The Anglophones, on the other hand, rated their future SWB in Quebec consistently lower than an unspecified future.

Access to health care services: East-End Montreal (Quebec) English-speaking elderly experience [master's thesis, McGill University] - Thomas, Rosemary Hellen. (2008)

Social networks and self-rated health in two French-speaking Canadian community dwelling populations over 65 - Zunzunegui, Maria Victoria; Koné, A.; Johri, Mira; Béland, François; Wolfson, Christina; Bergman, Howard (Social Science & Medicine, 2004)
The objective was to evaluate the associations between older persons’ health status and their social integration and social networks (family, children, friends and community), in two French-speaking, Canadian community dwelling populations aged 65 years and over, using the conceptual framework proposed by Berkman and Thomas. Data were taken from two 1995 surveys conducted in the city of Moncton (n=1518) and the Montreal neighbourhood of Hochelaga-Maisonneuve (n=1500). Social engagement (a cumulative index of social activities), networks consisting of friends, family and children and social support were measured using validated scales. Multiple logistic regressions based on structured inclusion of potentially mediating variables were fitted to estimate the associations between health status and social networks. Self-rated health was better for those with a high level of social integration and a strong network of friends in both locations. In addition, in Hochelaga-Maisonneuve family and children networks were positively associated with good health, though the effect of friend networks was attenuated in the presence of disability, good social support from children was associated with good health. Age, sex and education were included as antecedent variables; smoking, alcohol consumption, exercise, locus of control and depressive symptoms were considered intermediary variables between social networks and health. In conclusion, social networks, integration and support demonstrated unique positive associations with health. The nature of these associations may vary between populations and cultures.